EDUCAÇÃO FÍSICA EM SALA DE AULA: UMA ATIVIDADE VOLTADA PARA O DESENVOLVIMENTO HUMANO - ZAPAROLI, Willian Gomes (2022)
This work has as its theme “Physical education in the classroom: an activity focused on human development”. Its object of study is Physical Education in the classroom in a historical-cultural approach. Its general objective is to analyze how Physical Education has contributed to the human and social development of children and adolescents in Elementary School in municipal schools in Imperatriz-MA. As an initial step to support and situate the reader in the text, discussions were made related to the evolution of Physical Education and its insertion in the school environment, tracing a timeline in chronological order of the sequence of facts. Documentary research through official national and state curricula were important to investigate the possibilities for improvements in the approaches to classes. Throughout the investigation process, it was pertinent to delve deeper into elements of the basic training of the teachers participating in the research, family culture, influence of their years as a student, university education, initial experiences and subsequent years. We proposed as a way of approaching the research of a qualitative nature, where the most important thing was to collect the testimonies and impressions of the teachers' particularities. The choice of the type of semi-structured interview allowed us to obtain surprising and highly relevant testimonies for Educational research and for research in Physical Education in Schools. The transcription of many speeches showed teachers' knowledge and concern with pedagogical theories and with the dichotomy between cultural practices rooted in traditional teaching in the face of the possibilities of a pedagogical practice more aligned with progressive values in the teaching and learning process. It was evident in the filtering of the testimonies, we observed the great anguish and afflictions of the teachers with the directions that our education system has taken, the damages with the wrong use of technologies and mainly for the need to deconstruct an image of discredit of Physical Education. School for the Human development of individuals in order to avoid fragmentation between theory and practice.